Comparison of surgical pleth index-guided analgesia versus conventional analgesia technique in general anesthesia surgeries: A systematic review and meta-analysis - Xu, Xi; Zhang, Xue-Feng; Yu, Zi-Hang; Liu, Jian; Nie, Liang; Song, Jian-Li (Journal of clinical anesthesia, 2025)
The objective of this study is to investigate whether the use of surgical pleth index (SPI)-guided intraoperative analgesia can result in a reduction in opioid consumption, intraoperative circulatory fluctuations, and the incidence of postoperative adverse reactions when compared to conventional analgesia techniques. A comprehensive literature search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library from the inception of these databases to November 2024. The objective was to identify randomized controlled trials that compared the use of SPI-guided analgesia with conventional analgesia practices in adult patients who underwent general anesthesia. The primary outcome was the intraoperative consumption of opioids, while intraoperative circulatory fluctuations, postoperative opioid consumption, pain scores, and adverse events served as secondary outcomes. Standardized mean differences (SMDs), weighted mean differences (WMDs) or pooled risk ratios (RRs) along with the corresponding 95 % confidence intervals (CIs) were employed for analysis. Fourteen studies were included in our meta-analysis. The pooled results indicated no significant difference in intraoperative opioid consumption between the SPI-guided analgesia group and the control group (SMD = 0.16, 95 % CI: −0.15 to 0.47, p = 0.33). However, SPI-guided analgesia was found to reduce intraoperative propofol dosage (SMD = −0.31, 95 % CI: −0.54 to −0.08, p = 0.008), prevent intraoperative tachycardia (RR = 0.50, 95 % CI: 0.30 to 0.85, p = 0.011), and significantly shorten the eye-opening time (WMD = −1.89, 95 % CI: −2.47 to −1.31, p < 0.001). No statistically significant differences were observed in extubation time, postoperative nausea and vomiting, pain scores, or postoperative opioid consumption. Compared to the conventional analgesia group, SPI-guided analgesia does not reduce intraoperative opioid consumption in adult patients undergoing general anesthesia. Trial registration: The protocol for this meta-analysis has been registered in PROSPERO (CRD42024611690). •Effective analgesia prevents intraoperative complications and enhances patient outcomes.•Opioids are essential intraoperative analgesics; their improper use can adversely affect surgical outcomes.•SPI provides guidance on pain management, minimizing the risks of overdose and inadequate analgesia.